Secondary battery and electric device

By adding silicon-containing compounds and fluorocarbonate to the electrolyte of the secondary battery, controlling the structural parameters of the electrodes, building a low reactive interface layer, the problem of low energy efficiency of the secondary battery is solved and higher energy efficiency and stability are achieved.

CN119695234AActive Publication Date: 2025-03-25SUNWODA MOBILITY ENERGY TECHNOLOGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411848688.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-25
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

The energy efficiency of existing secondary batteries is low, which affects the charging and discharging performance of the batteries.

Method used

By adding silicon-containing compounds and fluorocarbonate to the electrolyte, controlling the single-sided density and number of stacked layers of the positive electrode sheet, as well as the height and width of the stacked battery cell, the SEI and CEI interface layers with lower reactivity are constructed to reduce the side reaction of the electrolyte.

Benefits of technology

Effectively reduce interface impedance, improve the energy efficiency of secondary batteries, enhance the low-temperature and high-temperature stability of the SEI interface layer, optimize the ionic conductivity of the interface film, and improve the wetting of the electrolyte.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005190031470000011
    Figure BDA0005190031470000011
  • Figure BDA0005190031470000031
    Figure BDA0005190031470000031
  • Figure BDA0005190031470000111
    Figure BDA0005190031470000111
Patent Text Reader

Abstract

The invention discloses a secondary battery and a power utilization device, and belongs to the technical field of batteries, the total content of a silicon-containing compound and fluorocarbonate in an electrolyte, the single-side surface density and the lamination layer number of a positive pole piece and the height and the width of a laminated battery cell are controlled to meet a certain relation, so that the infiltration speed can be effectively improved, and the battery efficiency is improved. The utilization rate of the positive electrode active material and the negative electrode active material is improved, the gas production of the secondary battery is reduced, the interface impedance is effectively reduced, and the energy efficiency of the secondary battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a secondary battery and an electrical device. Background Art

[0002] Secondary batteries have great advantages in the field of energy storage, but there are still some problems in practical applications. For example, the energy efficiency of secondary batteries is a key parameter that affects battery use and benefits. It determines the battery's ability to convert charge and discharge energy. Currently, the energy efficiency of secondary batteries based mainly on lithium iron phosphate still needs to be improved.

[0003] In view of this, this application is filed. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a secondary battery and an electrical device, which can effectively reduce the interface impedance and improve the energy efficiency of the secondary battery.

[0005] To achieve the above-mentioned object, the first aspect of the present application provides a secondary battery, comprising a laminated battery cell and an electrolyte, wherein the laminated battery cell comprises a positive electrode sheet, a negative electrode sheet, and a separator arranged in a stacked manner, and the electrolyte comprises a first additive, wherein the first additive comprises a silicon-containing compound and a fluorinated carbonate;

[0006] The secondary battery satisfies: 0.277≤Y≤11.076;

[0007]

[0008] Wherein, a% is the mass percentage of the first additive in the electrolyte;

[0009] b mg / mm 2 is the single-sided surface density of the positive electrode plate;

[0010] cm is the height of the laminated battery core;

[0011] dm is the width of the laminated battery core;

[0012] The e layer is the number of stacked layers of the positive electrode sheet.

[0013] As an implementation scheme of the present application, at least one of the following (1) to (5) is satisfied:

[0014] (1) 0.1≤a≤4;

[0015] (2) 0.08≤b≤0.3;

[0016] (3) 0.18 ≤ c ≤ 0.26;

[0017] (4) 0.16≤d≤0.5;

[0018] (5)66≤e≤125.

[0019] As an implementation scheme of the present application, at least one of the following (1) to (5) is satisfied:

[0020] (1)1≤a≤3;

[0021] (2) 0.15 ≤ b ≤ 0.26;

[0022] (3) 0.207≤c≤0.215;

[0023] (4) 0.17≤d≤0.4;

[0024] (5)76≤e≤120.

[0025] As an embodiment of the present application, the first additive includes a silicon-containing compound and a fluorocarbonate, and the mass ratio of the silicon-containing compound to the fluorocarbonate is (0.5-2):1.

[0026] As an embodiment of the present application, the silicon-containing compound includes at least one of tris(trimethylsilyl)phosphate and tris(trimethylsilyl)borate.

[0027] As an embodiment of the present application, the fluorinated carbonate comprises at least one of fluorinated ethylene carbonate, 4,5-difluoroethylene carbonate, 4,4,5,5-tetrafluoroethylene carbonate, and 4-trifluoromethylethylene carbonate.

[0028] As an embodiment of the present application, the electrolyte further includes a second additive and a third additive;

[0029] The second additive includes at least one of vinyl sulfate, 1,3-propane sultone, methylene disulfonate, propenyl-1,3-sultone, N,N'-sulfuryl diimidazole, triphenyl phosphite, n-butyric anhydride, hexane trinitrile, succinonitrile, and tetrafluoroterephthalonitrile;

[0030] The third additive includes at least one of lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium difluorobis(oxalatophosphate), lithium difluorophosphate, 4,5-dicyano-2-trifluoromethyl-imidazole lithium, and lithium trifluoromethanesulfonate.

[0031] As an embodiment of the present application, the mass percentage of the second additive in the electrolyte is 0.1-1%.

[0032] As an embodiment of the present application, the mass percentage of the third additive in the electrolyte is 0.05-0.5%.

[0033] As an embodiment of the present application, the second additive comprises vinyl sulfate, the third additive comprises lithium difluorooxalate borate, the vinyl sulfate accounts for F% by mass of the electrolyte, and the lithium difluorooxalate borate accounts for G% by mass of the electrolyte, satisfying: 0.1 <F<1,1≤F / G≤10。

[0034] As an embodiment of the present application, the electrolyte further includes a lithium salt, and the lithium salt includes at least one of lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate; the concentration of the lithium salt in the electrolyte is 0.5 to 1.3M.

[0035] A second aspect of the present application provides an electrical device, comprising the secondary battery described above, wherein the secondary battery serves as a power supply for the electrical device.

[0036] The beneficial effects of the present invention are as follows: by controlling the total content of silicon-containing compounds and fluorocarbonates in the electrolyte, the single-sided surface density and the number of stacked layers of the positive electrode sheet, and the height and width of the stacked battery cell to meet a certain relationship, the present application can construct SEI and CEI interface layers with lower reaction activity, reduce side reactions of the electrolyte, enhance the low-temperature stability and high-temperature stability of the SEI interface layer, inhibit oxidative decomposition of the electrolyte, optimize the ionic conductivity of the interface film, improve the wettability of the electrolyte, effectively increase the wetting speed, improve the utilization rate of the positive electrode active material and the negative electrode active material, reduce the gas production of the secondary battery, effectively reduce the interface impedance, and improve the energy efficiency of the secondary battery. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0038] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0039] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0040] The embodiment of the present application provides a secondary battery, including a laminated battery cell and an electrolyte, wherein the laminated battery cell includes a positive electrode sheet, a negative electrode sheet, and a separator arranged in a stacked manner, and the electrolyte includes a first additive, wherein the first additive includes a silicon-containing compound and a fluorinated carbonate;

[0041] The secondary battery satisfies: 0.277≤Y≤11.076, for example, it can be 0.277, 0.28, 0.3, 0.5, 0.8, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 11.076 or a range consisting of any two values ​​therein;

[0042]

[0043] Wherein, a% is the mass percentage of the first additive in the electrolyte;

[0044] b mg / mm 2 is the single-sided surface density of the positive electrode plate;

[0045] cm is the height of the laminated battery core;

[0046] dm is the width of the laminated battery core;

[0047] The e layer is the number of stacked layers of the positive electrode sheet.

[0048] The inventors of the present application have found that the electrochemical performance of the secondary battery has a significant correlation with the additives in the electrolyte, the single-sided surface density of the positive electrode sheet, the number of stacking layers, and the height and width of the stacked battery cell. By controlling the total content of silicon-containing compounds and fluorocarbonates in the electrolyte, the single-sided surface density and the number of stacking layers of the positive electrode sheet, and the height and width of the stacked battery cell to meet the relationship described in the present application, it is possible to construct SEI and CEI interface layers with lower reaction activity, reduce side reactions of the electrolyte, enhance the low-temperature stability and high-temperature stability of the SEI interface layer, inhibit oxidative decomposition of the electrolyte, optimize the ionic conductivity of the interface film, and improve the wettability of the electrolyte. It can effectively increase the wetting speed, improve the utilization rate of the positive electrode active material and the negative electrode active material, reduce the gas production of the secondary battery, effectively reduce the interface impedance, and improve the energy efficiency of the secondary battery.

[0049] In one embodiment, 1.948≤Y≤8.307, especially when the value of Y is controlled within this range, the interface impedance can be further reduced and the energy efficiency of the secondary battery can be improved.

[0050] In one embodiment, 0.1≤a≤4, for example, it can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.5, 2, 2.5, 3, 3.5, 4 or a range consisting of any two of the values. The present application controls the mass percentage of the first additive in the electrolyte within this range, thereby improving the thermal stability of the electrolyte, promoting the formation of more stable and less reactive SEI and CEI interface layers, reducing side reactions of the electrolyte and consumption of the electrolyte, inhibiting side reactions caused by metal ions in the positive electrode active material, improving the ionic conductivity of the SEI and CEI interface layers, increasing the migration rate of lithium ions, improving high and low temperature performance, further reducing interfacial impedance, and improving the energy efficiency of the secondary battery.

[0051] In one embodiment, 0.08≤b≤0.3, for example, it can be 0.08, 0.1, 0.12, 0.15, 0.2, 0.22, 0.25, 0.3 or a range consisting of any two of these values. By controlling the single-sided surface density of the positive electrode pole piece within this range, it is possible to promote the uniform distribution of the positive electrode active material on the positive electrode pole piece, reduce the migration and diffusion pathways of the active ions in the positive electrode active material, effectively reduce the internal resistance of the secondary battery, further reduce the gas production of the secondary battery, reduce the interface impedance, and improve the energy efficiency of the secondary battery.

[0052] Among them, in this application, the single-sided surface density test method of the positive electrode sheet is to cut the positive electrode sheet into a sheet with an area of ​​1540.25mm 2 The mass of the small disc is weighed with a high-precision balance, and the mass of the current collector is deducted and divided by the area of ​​the disc and then divided by 2 to calculate the single-sided surface density of the positive electrode.

[0053] In one embodiment, 0.18≤c≤0.26, for example, it can be 0.18, 0.2, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26 or a range consisting of any two of these values. By controlling the height of the stacked battery cell within this range, it is beneficial to increase the electrolyte infiltration rate of the electrode and improve the kinetic performance of the secondary battery.

[0054] In one embodiment, 0.16≤d≤0.5, for example, it can be 0.16, 0.18, 0.2, 0.22, 0.25, 0.28, 0.3, 0.32, 0.35, 0.38, 0.4, 0.42, 0.45, 0.48, 0.5 or a range consisting of any two of these values. By controlling the width of the stacked battery cell within this range, it is beneficial to reduce the electrode transmission impedance and improve energy efficiency.

[0055] In one embodiment, 66≤e≤125, for example, it can be 66, 70, 75, 80, 85, 90, 95, 100, 105, 110, 115, 120, 125 or a range consisting of any two of these values. By controlling the number of stacking layers of the positive electrode plate within this range, the capacity of the secondary battery can be effectively guaranteed and the energy density can be improved.

[0056] In one embodiment, 1≤a≤3, for example, it can be 1, 1.2, 1.5, 2, 2.5, 2.8, 3 or a range consisting of any two of these values.

[0057] In one embodiment, 0.15≤b≤0.26, for example, b may be 0.15, 0.16, 0.17, 0.18, 0.19, 0.2, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26 or a range consisting of any two of these values.

[0058] In one embodiment, 0.207≤c≤0.215, for example, it can be 0.207, 0.208, 0.209, 0.21, 0.211, 0.212, 0.213, 0.214, 0.215 or a range consisting of any two of them.

[0059] In one embodiment, 0.17≤d≤0.4, for example, it can be 0.17, 0.18, 0.2, 0.22, 0.25, 0.3, 0.32, 0.35, 0.38, 0.4 or a range consisting of any two of these values.

[0060] In one embodiment, 76≤e≤120, for example, it can be 76, 78, 80, 85, 90, 95, 100, 105, 110, 115, 120 or a range consisting of any two of the values.

[0061] In one embodiment, the first additive includes a silicon-containing compound and a fluorocarbonate, and the mass ratio of the silicon-containing compound to the fluorocarbonate is (0.5-2):1. The present application adopts a combination of a silicon-containing compound and a fluorocarbonate in a mass ratio of (0.5-2):1 as the first additive, which can more effectively improve the stability of the electrolyte, promote the formation of a more uniform and dense interface film, inhibit the decomposition and side reactions of the electrolyte under high voltage, further reduce the interfacial impedance, and improve the energy efficiency of the secondary battery.

[0062] In one embodiment, the silicon-containing compound includes at least one of tris(trimethylsilyl)phosphate and tris(trimethylsilyl)borate.

[0063] In one embodiment, the fluorinated carbonate comprises at least one of fluorinated ethylene carbonate, 4,5-difluoroethylene carbonate, 4,4,5,5-tetrafluoroethylene carbonate, and 4-trifluoromethylethylene carbonate.

[0064] In one embodiment, the electrolyte further includes a second additive and a third additive.

[0065] In one embodiment, the second additive includes at least one of vinyl sulfate, 1,3-propane sultone, methylene disulfonate, propenyl-1,3-sultone, N,N'-sulfuryl diimidazole, triphenyl phosphite, n-butyric anhydride, hexane trinitrile, succinonitrile, and tetrafluoroterephthalonitrile;

[0066] In one embodiment, the third additive includes at least one of lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium difluorobis(oxalatophosphate), lithium difluorophosphate, 4,5-dicyano-2-trifluoromethyl-imidazole lithium, and lithium trifluoromethanesulfonate.

[0067] The present application adopts the above three types of additives in combination, wherein the first additive effectively improves the initial interface film-forming stability of the negative electrode and reduces the internal resistance, the second additive improves the initial interface high-temperature film-forming interface stability of the positive and negative electrodes, and the third additive effectively ensures the film-forming interface state of the initial SEI inorganic layer of the secondary battery, forming structural functions such as low impedance, high temperature resistance, dense film formation, and high electronic insulation. After thermal runaway, the reaction activity of the polymer containing CF bond in the negative electrode active surface and the positive electrode sheet is reduced, thereby reducing H 2 It can effectively reduce the interface impedance and improve the energy efficiency of secondary batteries.

[0068] In one embodiment, the mass percentage of the second additive in the electrolyte is 0.1-1%, for example, it can be 0.1%, 0.2%, 0.5%, 0.6%, 0.8%, 1% or a range consisting of any two of these values. In particular, when the mass percentage of the second additive in the electrolyte is controlled within this range, a protective lower interface film with high temperature resistance and chemical stability is formed at the interface between the positive and negative electrodes, which effectively reduces side reactions at high temperature and alleviates corrosion to the positive and negative electrodes.

[0069] In one embodiment, the mass percentage of the third additive in the electrolyte is 0.05-0.5%, for example, it can be 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5% or a range consisting of any two of these values. In particular, when the mass percentage of the third additive in the electrolyte is controlled within this range, it can more effectively ensure the film-forming interface state of the initial SEI inorganic layer of the secondary battery, form structural functions such as low impedance, high temperature resistance, dense film formation, and high electronic insulation, reduce interface impedance, and improve the energy efficiency of the secondary battery.

[0070] In one embodiment, the second additive comprises vinyl sulfate, the third additive comprises lithium difluorooxalate borate, the vinyl sulfate accounts for F% by mass of the electrolyte, and the lithium difluorooxalate borate accounts for G% by mass of the electrolyte, satisfying: 0.1 <F<1,1≤F / G≤10。

[0071] In one embodiment, the electrolyte further includes a lithium salt, and the lithium salt includes at least one of lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate; the concentration of the lithium salt in the electrolyte is 0.5 to 1.3 M, for example, it can be 0.5 M, 0.6 M, 0.7 M, 0.8 M, 0.9 M, 1 M, 1.1 M, 1.2 M, 1.3 M or a range consisting of any two of the values.

[0072] In one embodiment, the electrolyte further includes an organic solvent, and the organic solvent includes cyclic carbonate and chain carbonate.

[0073] In one embodiment, the cyclic carbonate includes at least one of ethylene carbonate, vinylene carbonate, and propylene carbonate.

[0074] In one embodiment, the linear carbonate includes at least one of dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, and dipropyl carbonate.

[0075] In one embodiment, the mass percentage of the cyclic carbonate in the organic solvent is 30-40%, for example, it can be 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40% or a range consisting of any two values ​​therein.

[0076] In one embodiment, the mass percentage of the linear carbonate in the organic solvent is 60-70%, for example, it can be 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70% or a range consisting of any two values ​​therein.

[0077] In one embodiment, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, and the positive electrode active material layer includes a positive electrode active material.

[0078] In one embodiment, the positive electrode active material includes at least one of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, and lithium iron manganese phosphate.

[0079] In one embodiment, the positive electrode active material includes a chemical formula of Li a Fe 1-b M b PO 4 A compound wherein 0.8≤a≤1.2, 0≤b≤0.9, and M is selected from at least one of Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Ti, V, Mg, and Al.

[0080] In one embodiment, the type of the positive electrode current collector is not particularly limited, and it can be any known material suitable for use as a positive electrode current collector. In one embodiment, the positive electrode current collector includes metal materials such as aluminum, stainless steel, nickel plating, titanium, tantalum, and carbon materials such as carbon cloth and carbon paper.

[0081] There is no particular restriction on the form of the positive electrode current collector. When the positive electrode current collector is a metal material, the positive electrode current collector may be in the form of metal foil, metal cylinder, metal strip roll, metal plate, metal foil, metal plate mesh, stamped metal, foamed metal, etc. When the positive electrode current collector is a carbon material, the positive electrode current collector may include but is not limited to a carbon plate, a carbon film, a carbon cylinder, etc.

[0082] In one embodiment, the positive electrode active material layer further includes a conductive agent and a binder.

[0083] In one embodiment, the secondary battery further includes a negative electrode plate, the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, and the negative electrode active material layer includes a negative electrode active material.

[0084] In the present application, there is no particular limitation on the negative electrode current collector, as long as the purpose of the present application can be achieved, for example, it can be copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, foam nickel, foam copper or a composite current collector.

[0085] In one embodiment, the negative electrode active material can be natural graphite, artificial graphite, mesophase microcarbon beads (MCMB), hard carbon, soft carbon, silicon, silicon-carbon composite, SiO, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO 2, spinel structure lithium titanate Li 4 Ti 5 O 12 , at least one of Li-Al alloy and metallic lithium.

[0086] In one embodiment, the negative electrode active material layer further includes a conductive agent and a binder.

[0087] In one embodiment, the type of the conductive agent mentioned in the present application is not limited, and any known conductive agent can be used.

[0088] In one embodiment, the conductive agent includes at least one of carbon materials such as acetylene black, needle coke, carbon nanotubes, and graphene.

[0089] In one embodiment, the type of adhesive mentioned in the present application is not limited, and any known adhesive can be used.

[0090] In one embodiment, the binder includes at least one of polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, polyimide, aromatic polyamide, cellulose, nitrocellulose, styrene-butadiene rubber, nitrile rubber, fluororubber, isoprene rubber, polybutadiene rubber, ethylene-propylene rubber, styrene-butadiene-styrene block copolymer or its hydrogenate, ethylene-propylene-diene terpolymer, styrene-ethylene-butadiene-ethylene copolymer, styrene-isoprene-styrene block copolymer, isotactic-1,2-polybutadiene, polyvinyl acetate, ethylene-vinyl acetate copolymer, propylene-α-olefin copolymer, polyvinylidene fluoride, polytetrafluoroethylene, fluorinated polyvinylidene fluoride, and polytetrafluoroethylene-ethylene copolymer.

[0091] In the secondary battery mentioned in the present application, a separator is usually provided between the positive electrode and the negative electrode to prevent short circuit. The material and shape of the separator are not particularly limited as long as the effect of the present application is not significantly impaired.

[0092] In the secondary battery mentioned in the present application, a separator is usually provided between the positive electrode and the negative electrode to prevent short circuit. The material and shape of the separator are not particularly limited as long as the effect of the present application is not significantly impaired.

[0093] In one embodiment, the separator includes a porous sheet or non-woven fabric having excellent liquid retention. The materials of the resin or glass fiber separator include, but are not limited to, polyolefin, aromatic polyamide, polytetrafluoroethylene, polyethersulfone, and the like.

[0094] In one embodiment, the polyolefin is polyethylene or polypropylene. In some embodiments, the polyolefin is polypropylene. The materials of the above-mentioned diaphragm can be used alone or in any combination.

[0095] In one embodiment, the secondary battery may include an outer package, which can be used to encapsulate the electrode assembly and the electrolyte.

[0096] In one embodiment, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0097] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square, or any other shape.

[0098] An embodiment of the present application provides an electrical device, comprising the secondary battery described above.

[0099] Exemplarily, the above-mentioned electrical devices may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0100] The present application is further described below with specific embodiments:

[0101] Example 1

[0102] Embodiment 1 provides a secondary battery, including a laminated battery cell, wherein the laminated battery cell has a height of 207 mm, a width of 352 mm, and a thickness of 71.5 mm, and a method for preparing the secondary battery comprises the following steps:

[0103] (1) Preparation of positive electrode sheet

[0104] LiFePO 4 ), acetylene black (Super P), polyvinylidene fluoride (PVDF), and polyether phosphate are mixed uniformly in a mass ratio of 97.55:1.8:0.5:0.15, and uniformly dispersed in N-methyl-2-pyrrolidone (NMP) to form a uniform positive electrode slurry. The mixed positive electrode slurry is coated on both sides of the aluminum foil, and then baked, rolled, and cut into pieces to obtain a positive electrode sheet, wherein the density PD of the positive electrode active material layer is 2.6g / cm 3 .

[0105] (2) Preparation of negative electrode sheet

[0106] Graphite, acetylene black (Super P), CMC (sodium carboxymethyl cellulose), SBR (styrene butadiene rubber), and PAA (polyacrylic acid) were mixed evenly in a mass ratio of 96.7:0.7:0.6:1.5:0.5, and evenly dispersed in deionized water to form a uniform black slurry. The mixed slurry was coated on both sides of the copper foil, and then baked, rolled, and cut into pieces to obtain the negative electrode sheet, wherein the density PD of the negative electrode active material layer is 1.6 g / cm 3 .

[0107] (3) Preparation of electrolyte

[0108] At room temperature, in a glove box filled with argon (H 2 O<1ppm,O 2 <1ppm), mix DMC, EMC and EC in a volume ratio of 30:30:40 and use The molecular sieve removes water and converts 6% LiFSI and 6% LiPF 6 Add gradually to the obtained mixed solvent, continue stirring and cool down, ensure that the electrolyte temperature does not rise by more than 2°C, continue to add lithium salt, and finally obtain a colorless transparent liquid, add 0.50wt% of tris(trimethylsilyl) phosphate (TMSP) equivalent to the total mass of the electrolyte, 0.50wt% of vinyl sulfate (DTD), 0.50wt% of fluoroethylene carbonate (FEC), and 0.2wt% of lithium difluorooxalatoborate (LiODFB) and stir evenly to obtain the electrolyte described in the present application.

[0109] (4) Assembly of secondary batteries:

[0110] The positive electrode sheet, the separator (Xingyuan material PE (9μm) + ceramic (2μm) + glue layer (5μm) + glue layer (5μm), with a total thickness of 21μm) and the negative electrode sheet are stacked in sequence, with the separator being between the positive electrode sheet and the negative electrode sheet, and a battery cell is obtained after stacking; the battery cell is encapsulated in a square aluminum shell, dried, and injected with 2400g of electrolyte, and a secondary battery is obtained after infiltration, formation, sealing, and capacity division.

[0111] The parameters of Example 1 are shown in Table 1.

[0112] Examples 2 to 8, Comparative Examples 1 to 3

[0113] The difference between Examples 2 to 8 and Comparative Examples 1 to 3 and Example 1 is that Examples 2 to 8 and Comparative Examples 1 to 3 adjust the dosage of FEC and TMSP, and then adjust the value of a, as shown in Table 1 for details.

[0114] Examples 9 to 13, Comparative Examples 4 to 5

[0115] The difference between Examples 9 to 13 and Comparative Examples 4 to 5 and Example 1 is that Examples 9 to 13 and Comparative Examples 4 to 5 adjust b and e by adjusting the coating amount of the positive electrode slurry on the current collector and the number of stacked layers of the positive electrode sheets, as shown in Table 1 for details.

[0116] Embodiments 14 to 17

[0117] The difference between Examples 14 to 17 and Example 1 is that Examples 14 to 17 adjust the value of c, as shown in Table 1 for details.

[0118] Examples 18 to 22

[0119] The difference between Examples 18 to 22 and Example 1 is that Examples 18 to 22 adjust the value of d, as shown in Table 1 for details.

[0120] Comparative Examples 6-7

[0121] The difference between Comparative Examples 6 and 7 and Example 1 is that the values ​​of c and d are adjusted in Comparative Examples 6 and 7, as shown in Table 1 for details.

[0122] Table 1

[0123]

[0124] Embodiments 23 to 27

[0125] The difference between Examples 23 to 27 and Example 1 is that the contents of DTD and LiODFB in the electrolyte of the secondary batteries described in Examples 23 to 27 are different, as shown in Table 2 for details.

[0126] Table 2

[0127]

[0128] Test Case

[0129] Room temperature DCR test method: At 25±2°C, the secondary batteries of the embodiments and comparative examples were charged to 3.65V at 0.5C, then discharged at 0.5C for 60min, adjusted to 50% SOC, and then discharged at 1C constant current pulse for 10s. DCR was calculated as (voltage before pulse discharge - voltage after pulse discharge) / discharge current. The test results are shown in Table 3.

[0130] Energy efficiency test method: At 25±2°C, the secondary batteries of the embodiment and comparative example are charged to 3.65V at 0.5P charging power, and then discharged to 2.5V at 0.5P discharging power. Energy efficiency is calculated as discharge energy / charge energy*100%. The test results are shown in Table 3.

[0131] High and low temperature performance test method (high and low temperature energy efficiency): At 5±2°C and 45±2°C, the secondary batteries of the embodiments and comparative examples are charged to 3.65V at a charging power of 0.5P, and then discharged to 2.5V at a discharging power of 0.5P. The energy efficiency is calculated as follows: discharge energy / charge energy*100%. The test results are shown in Table 3.

[0132] Table 3

[0133]

[0134]

[0135] As can be seen from Table 3, the present application controls the total content of silicon-containing compounds and fluorocarbonates in the electrolyte, the single-sided surface density and the number of stacked layers of the positive electrode sheet, and the height and width of the laminated battery cell to satisfy a certain relationship, thereby being able to construct SEI and CEI interface layers with lower reaction activity, reduce side reactions of the electrolyte, enhance the low-temperature stability and high-temperature stability of the SEI interface layer, inhibit oxidative decomposition of the electrolyte, optimize the ionic conductivity of the interface film, and improve the wettability of the electrolyte. It can effectively increase the wetting speed, improve the utilization rate of the positive electrode active material and the negative electrode active material, reduce the gas production of the secondary battery, effectively reduce the interface impedance, and improve the energy efficiency of the secondary battery.

[0136] It can be seen from the comparison of Examples 1 to 4 that by controlling the mass percentage of the first additive in the electrolyte to 1% to 3%, the interface impedance can be further reduced and the energy efficiency of the secondary battery can be improved.

[0137] Comparing Examples 1, 5 to 8, it can be seen that the present invention can further reduce the interface impedance and improve the energy efficiency of the secondary battery by using the silicon-containing compound and the fluorinated carbonate in a mass ratio of (0.5 to 2):1 as the first additive.

[0138] Comparison of Examples 1 and 9 to 13 shows that by controlling 0.15≤b≤0.26 and 76≤e≤120, the interface impedance can be further reduced and the energy efficiency of the secondary battery can be improved.

[0139] Comparing Examples 1 with 14 to 17, it can be seen that by controlling 0.207≤c≤0.215, the interface impedance can be further reduced and the energy efficiency of the secondary battery can be improved.

[0140] Comparing Examples 1 with 18 to 22, it can be seen that by controlling 0.17≤d≤0.4, the interface impedance can be further reduced and the energy efficiency of the secondary battery can be improved.

[0141] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A secondary battery, comprising a laminated battery cell and an electrolyte, wherein the laminated battery cell comprises a positive electrode sheet, a negative electrode sheet, and a separator arranged in a stacked manner, characterized in that: The electrolyte includes a first additive, wherein the first additive includes a silicon-containing compound and a fluorocarbonate; The secondary battery satisfies: 0.277≤Y≤11.076; Wherein, a% is the mass percentage of the first additive in the electrolyte; b mg / mm 2 is the single-sided surface density of the positive electrode plate; cm is the height of the laminated battery core; dm is the width of the laminated battery core; The e layer is the number of stacked layers of the positive electrode sheet.

2. The secondary battery according to claim 1, characterized in that: Satisfy at least one of the following (1) to (5): (1)0.1≤a≤4; (2)0.08≤b≤0.3; (3)0.18≤c≤0.26; (4)0.16≤d≤0.5; (5)66≤e≤125。 3. The secondary battery according to claim 2, characterized in that: Satisfy at least one of the following (1) to (5): (1)1≤a≤3; (2)0.15≤b≤0.26; (3)0.207≤c≤0.215; (4)0.17≤d≤0.4; (5)76≤e≤120。 4. The secondary battery according to claim 1, characterized in that: The first additive includes a silicon-containing compound and a fluorinated carbonate, and the mass ratio of the silicon-containing compound to the fluorinated carbonate is (0.5-2):

1.

5. The secondary battery according to claim 1 or 4, characterized in that: The silicon-containing compound includes at least one of tris(trimethylsilyl)phosphate and tris(trimethylsilyl)borate; And / or, the fluorinated carbonate comprises at least one of fluorinated ethylene carbonate, 4,5-difluoroethylene carbonate, 4,4,5,5-tetrafluoroethylene carbonate, and 4-trifluoromethylethylene carbonate.

6. The secondary battery according to claim 1, characterized in that: The electrolyte further includes a second additive and a third additive; The second additive includes at least one of vinyl sulfate, 1,3-propane sultone, methylene disulfonate, propenyl-1,3-sultone, N,N'-sulfuryl diimidazole, triphenyl phosphite, n-butyric anhydride, hexane trinitrile, succinonitrile, and tetrafluoroterephthalonitrile; The third additive includes at least one of lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium difluorobis(oxalatophosphate), lithium difluorophosphate, 4,5-dicyano-2-trifluoromethyl-imidazole lithium, and lithium trifluoromethanesulfonate.

7. The secondary battery according to claim 6, characterized in that: The mass percentage of the second additive in the electrolyte is 0.1-1%; And / or, the mass percentage of the third additive in the electrolyte is 0.05-0.5%.

8. The secondary battery according to claim 6, characterized in that: The second additive comprises vinyl sulfate, and the third additive comprises lithium difluorooxalate borate, the mass percentage of the vinyl sulfate in the electrolyte is F%, and the mass percentage of the lithium difluorooxalate borate in the electrolyte is G%, satisfying: 0.1 <F<1,1≤F / G≤10。 9. The secondary battery according to claim 1, characterized in that: The electrolyte further includes a lithium salt, and the lithium salt includes at least one of lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate; the concentration of the lithium salt in the electrolyte is 0.5-1.3M.

10. An electrical device, characterized in that: It comprises the secondary battery according to any one of claims 1 to 9, wherein the secondary battery is used as a power supply for the electrical device.

Citation Information

Patent Citations

  • Secondary battery and electric device

    CN118263525A

  • Secondary battery and electric device

    CN118841518A

  • Positive electrode plate and lithium-ion secondary battery containing same

    US20240282949A1

  • Lithium-ion battery

    WO2024139584A1

  • Electrolyte for secondary battery, secondary battery, battery module, battery pack, and electrical device

    WO2024152720A1